КРИТЕРИИ ГОТОВНОСТИ К БРАКУ - Утепбергенов, М.А. (SCIENCE and SOCIETY, 2019)
The article deals with the process of preparation of the youth to the family life. For the first time the attempt was made to work out the social-psychological criteria of defining of the youth’s preparation to the marriage which can be the basis of the firmness and stability of family relationships.
Keywords: criteria of readiness to the marriage; culture of communication; marriage partner; conflict situations(marital conflict); matrimonial communication; firmness of marriage